Microglia response and in vivo therapeutic potential of methylprednisolone-loaded dendrimer nanoparticles in spinal cord injury - Cerqueira, Susana R. (2013)
The control and manipulation of cells that trigger secondary mechanisms following spinal cord injury (SCI) is one of the fi rst opportunities to minimize its highly detrimental outcomes. Herein, the ability of surface-engineered carboxymethylchitosan/ polyamidoamine (CMCht/PAMAM) dendrimer nanoparticles to intracellularly deliver methylprednisolone (MP) to glial cells, allowing a controlled and sustained release of this corticosteroid in the injury site, is investigated. The negatively charged MP-loaded CMCht/PAMAM dendrimer nanoparticles with sizes of 109 nm enable a MP sustained release, which is detected for a period of 14 days by HPLC. In vitro studies in glial primary cultures show that incubation with 200 μ g mL − 1 nanoparticles do not affect the cells’ viability or proliferation, while allowing the entire population to internalize the nanoparticles. At higher concentrations, microglial cell viability is proven to be affected in response to the MP amount released. Following lateral hemisection lesions in rats, nanoparticle uptake by the spinal tissue is observed 3 h after administration. Moreover, signifi cant differences in the locomotor output between the controls and the MP-loaded nanoparticle-treated animals one month after the lesion are observed. Therefore, MP-loaded CMCht/PAMAM dendrimer nanoparticles may prove to be useful in the reduction of the secondary injury following SCI.